Surto de dermatofilose em bezerros Nelore criados extensivamente em Goiás - Câmara, Antônio Carlos Lopes; Silva, Ana Bárbara Rocha; de Castro, Márcio Botelho; Silva, Anahí Souza; Perecmanis, Simone; Borges, José Renato Junqueira (Acta Scientiae Veterinariae, 2017)
Background: Dermatophilosis is an infectious-contagious disease of acute, subacute or chronic evolution caused by the etiologic agent Dermatophilus congolensis, and presents as hyperplastic or exudative dermatitis with crusty and scaly skin eruptions. Although it is a disease with important economic impact on Brazilian beef cattle, the reports of outbreaks in zebu cattle are restricted to the states of São Paulo and Mato Grosso do Sul. The present paper aimed to report the epidemiological, clinical, laboratorial and pathological findings of a dermatophilosis outbreak in Nelore calves raised extensively in Goiás, Midwestern Brazil. Case: An outbreak of skin lesions in Nelore calves occurred on a farm located in Cocalzinho de Goiás, Goiás, Midwestern Brazil. Fifty one (25.5%) of the 200 calves from 3-11-months-old presented cutaneous lesions. Forty nine of the calves were still suckling and two were weaned recently, and the most affected calves were offspring’s of cows with the lowest body condition score. Three severely affected calves were clinically examined presenting regular body condition score, pale pink ocular mucosa, fever (39.2-40.3°C), tachycardia (80-100 beats per minute), tachypnea (48-56 breaths per minute) and moderate presence of ticks. Skin inspection revealed crusty, elevated, non-pruritic lesions of grayish color that easily detached from the skin exposing a humid and hemorrhagic superficial lesion with pus. Lesions were widespread on the body with predominance on the face, ears, neck and dorsal region. Hematological findings of these calves presented leukocytosis (16,083 ± 1,910/µL) by netrophilia (11,121 ± 2,349/µL) and hyperfibrinogenemia (966.6 ± 208.16 mg/dL). Biochemical alterations consisted of hypoproteinemia (6.5 ± 0.5 g/dL) and a slight increase in GGT activity in two calves (28 and 19 U/L, respectively). Skin lesions samples were stained by Giemsa and demonstrated filaments presenting characteristic “train tracks” pattern, formed by parallel chains of cocci. Microscopic findings consisted of suppurative superficial dermatitis associated with intralesional bacteria. Histological sections stained by Gram revealed typical branched filamentous structures formed by multiple rows of Gram positive spherical cocci. Initially, treatment consisted in improve the herd body condition score and ticks control. Calves were treated for dermatophilosis with streptomycin (25 mg.kg-1, s.i.d., intramuscularly [IM], four days) and chlorhexidine diglylate 2% baths with manual crusts removal. Due to relapse in most calves caused by sub dosages by the owner, long-acting oxytetracycline (20 mg.kg-1, q48 h, IM, three doses) and stable disinfection was recommended. One year after this outbreak, the owner stated that there were no new cases on the farm. Discussion: Definitive diagnosis of dermatophilosis in the calves of this report was conducted by the association of epidemiological, clinical, cytological and histological findings. In the present report, predisposing factors such as low body condition score due to food shortage, micro injuries on the skin caused by ticks infestation and mechanical trauma by Brachiaria brizantha, and high temperatures, possibly acted synergistically causing this outbreak. Dermatophilosis treatment with long-acting oxytetracycline associated with topical treatment and environment disinfection allowed clinical cure and prevention of new cases in this farm. Long-acting oxytetracycline presents good results in the treatment of natural cases of dermatophilosis, reaching cure rates varying from 71.4 to 100%. Outbreaks of dermatophilosis in Nelore calves in Goiás may cause significant losses in beef cattle productivity and measures of control and prophylaxis should be considered for prevention.